Biomechanical analysis of lower extremity joints according to landing types during maximum vertical jump after jump landing in youth sports athletes - Park, J.; Kim, J. N.; Yoon, S. (Korean Journal of Sport Biomechanics, 2023)
Objective: The purpose of this study was to find out kinematic and kinetic differences the lower extremity joint according to the landing type during vertical jump movement after jump landing, and to present an efficient landing method to reduce the incidence of injury in youth players. Method: Total of 24 Youth players under Korean Sport and Olympic Committee, who used either heel contact landing (HCG) or toe contact landing (TCG) participated in this study (HCG (12): CG height: 168.7 ± 9.7 cm, weight: 60.9 ± 11.6 kg, age: 14.1 ± 0.9 yrs., career: 4.3 ± 2.9 yrs., TCG height: 174.8 ± 4.9 cm, weight: 66.9 ± 9.9 kg, age 13.9 ± 0.8 yrs., career: 4.7 ± 2.0 yrs.). Participants were asked to perform jump landing consecutively followed by vertical jump. A 3-dimensional motion analysis with 19 infrared cameras and 2 force plates was performed in this study. To find out the significance between two landing styles independent t-test was performed and significance level was set at .05. Results: HCG showed a significantly higher dorsi flexion, extension and flexion angle at ankle, knee and hip joints, respectively compared with those of TCG.